Polymer with main chain containing diphenylethane and side chain containing quaternary ammonium salt structure, synthesis method of polymer and application of polymer in field of water electrolysis hydrogen production

By using polymers containing diphenylethane in the electrolytic water-making hydrogen film electrode with the main chain and quaternary ammonium salt structure as the binder, the problems of poor charge transport capability and electrolytic performance of traditional binders are solved, and more efficient charge transport and longer service life are achieved.

CN119955043APending Publication Date: 2025-05-09SUQIAN GREEN ENERGY HYDROGEN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510128273.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The charge transport capability and electrolytic water-making performance of traditional electrolytic water-making hydrogen film electrode binders are poor, resulting in a reduced catalytic layer separation and charge transport capability.

Method used

The polymer with the main chain containing diphenylethane and the side chain containing quaternary ammonium salt structure is used as the binder. By introducing a highly hydrophobic main chain structure and a hydrophilic quaternary ammonium side chain structure, the microphase separation of the polymer is regulated to form a charge transport channel.

Benefits of technology

It improves charge transport capability and electrolytic performance, enhances the dispersion and utilization of the catalyst, and extends the service life of the membrane electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955043A_ABST
    Figure CN119955043A_ABST
Patent Text Reader

Abstract

The invention provides a polymer with a main chain containing diphenylethane and a side chain containing a quaternary ammonium salt structure, a synthesis method of the polymer and application of the polymer in the field of water electrolysis hydrogen production. The preparation method of the polymer with the main chain containing diphenylethane and the side chain containing quaternary ammonium salt comprises the following steps: reacting a diaryl alkane compound, 2, 2, 2-trifluoroacetophenone, N-methylpiperidone and dichloromethane under the action of a superacid catalyst, pouring the mixture into water to obtain a fibrous polymer, removing redundant acid in the polymer by using a sodium hydroxide aqueous solution, and drying to obtain the polymer with the main chain containing diphenylethane and the side chain containing quaternary ammonium salt. Washing and drying to obtain a polymer intermediate; and reacting the polymer intermediate and a halide in an organic solvent, adding acetone to precipitate a solid substance, washing, and drying to obtain the polymer with the main chain containing diphenylethane and the side chain containing quaternary ammonium salt. According to the polymer disclosed by the invention, microphase separation of the polymer is regulated and controlled by introducing a high-hydrophobic main chain structure and a hydrophilic quaternary ammonium side chain structure, and formation of a charge transfer channel on a membrane electrode is facilitated, so that the charge transfer capability and the water electrolysis performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polymer technology, and in particular to a polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain, a synthesis method thereof, and application thereof in the field of hydrogen production by electrolysis of water. Background Art

[0002] With the increasing proportion of renewable energy such as wind and solar energy in the energy structure, green hydrogen production technology that can adapt to fluctuating energy sources is particularly important. The hydrogen production technologies currently on the market can be divided into low-temperature, medium-temperature and high-temperature water electrolysis technologies. However, medium-temperature and high-temperature electrolyzers are most suitable for operation under constant load conditions and are not easy to start / stop frequently, which limits their application in dealing with fluctuating intermittent energy sources such as wind and solar energy. In this context, only low-temperature water electrolysis technology can meet the requirements. The two low-temperature electrolysis technologies currently on the market are AEMWE (anion exchange membrane water electrolysis) and PEMWE (proton exchange membrane water electrolysis). PEMWE faces the challenges of improving hydrogen production efficiency and reducing costs in recent developments, resulting in a decline in market confidence, which has also prompted the industry to shift its attention to another low-temperature water electrolysis technology-AEMWE.

[0003] At present, anion exchange membrane water electrolysis technology is an important technology in the field of new energy and clean energy technology, and the catalyst layer (catalyst and binder) is an important component of anion exchange membrane water electrolysis hydrogen production, and it is also the place where the water electrolysis hydrogen production reaction occurs. On the one hand, the binder connects the electrode catalyst and the anion exchange membrane to improve the interface compatibility between the two; on the other hand, as a dispersant for the electrode catalyst, it optimizes the three-phase interface structure of the reaction gas, ion and electron conduction, accelerates proton conduction, and improves the utilization rate of the catalyst.

[0004] Conventional binders include trimethylammonium functionalized polystyrene (TMA-x), cross-linked poly(norbornene), benzylated poly(hexamethyl-p-triphenylbenzimidazole) and poly(norbornene) terpolymer binders. These binders will swell when absorbing water. Excessive water absorption will cause the catalytic layer to separate, affecting the charge transfer capacity and thus reducing the performance of water electrolysis. Summary of the invention

[0005] The purpose of the present invention is to address the problems of poor charge transfer capacity and water electrolysis performance of conventional electrolytic water hydrogen production membrane electrode binders, and to propose a polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain. The polymer introduces a highly hydrophobic main chain structure and a hydrophilic quaternary ammonium side chain structure to regulate the microphase separation of the polymer, which is beneficial to the formation of a charge transfer channel on the membrane electrode, thereby improving the charge transfer capacity and water electrolysis performance.

[0006] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain, the general formula of which is shown in Formula I:

[0008]

[0009] In Formula I, x and 100-x represent molar percentages, and x is selected from 10 to 100 (for example, x is 70, 75, 80, 85, 90 or 100);

[0010] R is one or both of the following two structures;

[0011]

[0012] Wherein, m is an integer, which is selected as 0≤m≤20.

[0013] Furthermore, the number average molecular weight of the polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain is 4000-17000.

[0014] Another object of the present invention is to disclose a method for preparing a polymer containing diphenylethane in the main chain and a quaternary ammonium salt in the side chain, comprising the following steps:

[0015] (1) Synthesis of polymer precursors

[0016] Under the condition of -5-10°C, a diaryl alkane compound, 2,2,2-trifluoroacetophenone and N-methylpiperidone are placed in a reaction kettle, dichloromethane is added, and the reaction is carried out for 10-72 hours under the action of a super acid catalyst. After the reaction is completed, the mixture is poured into water to obtain a fibrous polymer, and the excess acid in the polymer is removed with a sodium hydroxide aqueous solution, and then the polymer is washed with deionized water until the pH is neutral, and then dried at 60-85°C for 12-24 hours to obtain a polymer intermediate;

[0017] (2) Synthesis of quaternary ammonium polymers

[0018] The polymer intermediate and the halide are added to an organic solvent, wherein the halide is a halogenated alkane or a halogenated chain quaternary ammonium salt, and the reaction is carried out at 25-80° C. for 24-48 hours. After the reaction is completed, acetone is added to precipitate a solid substance, which is washed and dried to obtain a polymer (binder) containing diphenylethane in the main chain and a quaternary ammonium salt in the side chain.

[0019] Furthermore, in step (1), the molar ratio of the diaryl alkane compound, 2,2,2-trifluoroacetophenone and N-methylpiperidone is 1:0.12-0.49:1.94-2.31, and the molar ratio of the diaryl alkane compound, dichloromethane and superacid catalyst is 1:11-13:21-23.

[0020] Furthermore, the superacid catalyst is one or more of trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid and tellurium pentafluoride.

[0021] Furthermore, the diarylalkane compound is one or more of diphenylmethane, diphenylethane, diphenylhexane and diphenyldecane.

[0022] Furthermore, the molar ratio of the polymer intermediate to the halogenated compound is 1:2-3; the mass ratio of the polymer intermediate to the organic solvent is 1:6-9; and the volume ratio of the organic solvent to acetone is 1:3-6.

[0023] Furthermore, the reaction time of step (1) is 48-72h.

[0024] Furthermore, the excess acid in step (1) is trifluoromethanesulfonic acid and trifluoroacetic acid.

[0025] Furthermore, the concentration of the sodium hydroxide aqueous solution in step (1) is 0.5-2M.

[0026] Furthermore, the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

[0027] Furthermore, the halogenated alkane is one or more of methyl iodide, 1-bromobutane and 1-chloropentane.

[0028] Furthermore, the halogenated chain quaternary ammonium salt is one or more of (3-bromopropyl)trimethylammonium bromide, (5-bromopentyl)trimethylammonium bromide and (6-bromohexyl)trimethylammonium bromide.

[0029] The preparation principle of the polymer containing diphenylethane in the main chain and quaternary ammonium salt in the side chain of the present invention is shown in Formula II:

[0030]

[0031] The main chain is obtained by condensation reaction of N-methylpiperidone, 2,2,2-trifluoroacetophenone and diphenylethane monomers, wherein x and 100-x represent molar percentages, and x is selected from 10-100 (for example, x is 70, 75, 80, 85, 90 or 100); the number average molecular weight of the polymer is 4000-17000.

[0032] R is one or more of the following two structures;

[0033]

[0034] m is an integer, selected to be 0≤m≤20.

[0035] Another object of the present invention is to disclose the application of a polymer containing diphenylethane in the main chain and a quaternary ammonium salt in the side chain in the field of hydrogen production by water electrolysis.

[0036] Furthermore, the polymer containing diphenylethane in the main chain and quaternary ammonium salt in the side chain is used in the field of binders for hydrogen production by water electrolysis.

[0037] Furthermore, the polymer containing diphenylethane in the main chain and quaternary ammonium salt in the side chain is used in the field of binders for catalysts for hydrogen production by electrolysis of water.

[0038] Another object of the present invention is to disclose a membrane electrode, comprising an anion exchange membrane and a cathode catalyst layer and an anode catalyst layer respectively located on both sides of the anion exchange membrane, wherein the cathode catalyst layer and the anode catalyst layer both comprise the polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain and a catalyst.

[0039] Furthermore, the content of the polymer containing diphenylethane in the main chain and quaternary ammonium salt structure in the side chain in the catalytic layer is 4-6wt%.

[0040] Furthermore, the catalyst is an active catalyst NiFeP / CNT.

[0041] Furthermore, the loading amount of the active catalyst NiFeP / CNT in the catalytic layer is 0.4-0.8 mg / cm 2 .

[0042] Another object of the present invention is to disclose a method for preparing a membrane electrode, comprising the following steps:

[0043] The catalyst and a binder solution containing diphenylethane in the main chain and a polymer containing a quaternary ammonium salt structure in the side chain are uniformly dispersed by ultrasonic dispersion to obtain catalyst ink, and the catalyst ink is sprayed on both sides of the anion exchange membrane to prepare a membrane electrode.

[0044] Furthermore, the mass ratio of the catalyst and the binder solution containing a polymer having diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain is 1:9-9:1, and the preferred mass ratio is 1:3-1:1.

[0045] Furthermore, the binder solution containing a polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain comprises: a polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain, dimethyl sulfoxide and ethanol (the mass ratio of dimethyl sulfoxide to ethanol is 1:0.5-0.5:1), and the concentration of the polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the binder solution is 18-25wt%, preferably 23wt%.

[0046] Furthermore, the catalyst is an active catalyst NiFeP / CNT.

[0047] The main chain of the polymer of the present invention is obtained by condensation reaction of N-methylpiperidone (also known as N-methyl-4-piperidone), 2,2,2-trifluoroacetophenone and diphenylethane monomer (also known as 1,2-diphenylethane); the polymer side chain carries a quaternary ammonium salt structure through a substitution reaction. Specifically, the present invention has the following advantages compared with the prior art:

[0048] (1) The main chain of the present invention is a diphenylethane skeleton without ether bonds, which can effectively increase the hydrophobicity and stability of the polymer main chain.

[0049] (2) The hydrophilic quaternary ammonium salt side chain and the strongly hydrophobic diphenylethane main chain of the present invention effectively regulate the microphase separation of the polymer, which is conducive to the formation of charge transfer channels by the polymer and improves the performance of hydrogen production by electrolysis of water. The polymer prepared by the present invention, which contains diphenylethane in the main chain and quaternary ammonium salt structure in the side chain, has the advantages of good stability and microphase separation as a binder, and at the same time ensures that the anion exchange membrane water electrolysis membrane electrode assembly has the advantages of low membrane surface resistance, high ion exchange capacity and long service life, and can be used in the field of hydrogen production by electrolysis of water.

[0050] (3) The polymer containing diphenylethane in the main chain and quaternary ammonium salt structure in the side chain of the present invention is used as a small molecular weight binder, which can effectively and firmly combine the catalyst and the anion exchange membrane, thereby improving the dispersibility of the catalyst.

[0051] In summary, the present invention introduces a diphenylethane structure into the main chain, so that the polymer has an aromatic skeleton without an ether bond, which is used as a binder to improve the stability of the catalyst layer; its hydrophilic quaternary ammonium salt side chain and the strongly hydrophobic diphenylethane main chain effectively regulate the microphase separation of the polymer, which is conducive to the formation of a charge transfer channel by the polymer and improves the performance of hydrogen production by electrolysis of water. The polymer containing diphenylethane in the main chain and quaternary ammonium salt structure in the side chain of the present invention has good application prospects and large-scale production potential in the field of hydrogen production by electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The nuclear magnetic resonance hydrogen spectrum of the polymer prepared in Example 1 containing diphenylethane in the main chain and quaternary ammonium salt structure in the side chain in deuterated dimethyl sulfoxide;

[0053] Figure 2 Schematic diagram of microphase separation of a polymer binder containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain prepared in Example 1;

[0054] Figure 3 This is a scanning electron microscope image of a membrane electrode prepared in Example 2 containing a polymer binder containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain;

[0055] Figure 4 Schematic diagram of microphase separation of the binder containing alkane side chains prepared in Comparative Example 1;

[0056] Figure 5 This is a scanning electron microscope image of a membrane electrode containing an alkane side chain binder prepared in Comparative Example 1;

[0057] Figure 6 The linear sweep voltammetry curves of hydrogen evolution of the membrane electrode prepared in Example 2 and Comparative Example 1 in hydrogen production by electrolysis of water;

[0058] Figure 7 The linear sweep voltammetry curves of oxygen evolution of the membrane electrode prepared in Example 2 and Comparative Example 1 in hydrogen production by electrolysis of water;

[0059] Figure 8 Schematic diagram of electrolysis current attenuation of the membrane electrode prepared in Example 2 in hydrogen production by water electrolysis. DETAILED DESCRIPTION

[0060] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0061] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0062] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0063] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0064] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0065] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0066] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0067] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0068] Example 1

[0069] This embodiment discloses a polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain, and its preparation principle is shown in Formula III:

[0070]

[0071] Specifically, the preparation method of the polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain comprises the following steps:

[0072] Synthesis of S01 polymer intermediates

[0073] Diphenylethane (39.73 g, 0.218 mol), m-terphenyl (24.73 g, 0.107 mol), N-methylpiperidone (30 g, 0.265 mol) and dichloromethane (86 mL) were added into a 1000 mL reactor, and the temperature was lowered to -5-0 ° C. Trifluoromethanesulfonic acid (370.64 g, 2.47 mol) and trifluoroacetic acid (35.31 g, 0.31 mol) were slowly added dropwise; after the addition was completed, the mixture was kept warm at 0 ° C, stirred and reacted for 48 hours, and the red-black viscous liquid obtained by the reaction was poured into water to obtain a fibrous polymer. The excess trifluoromethanesulfonic acid and trifluoroacetic acid in the polymer were removed with a 1M sodium hydroxide aqueous solution, and then washed with deionized water until the pH was neutral, and dried to obtain 71.66 g of a polymer intermediate with a yield of 87.8%.

[0074] Preparation of S02 binder:

[0075] Into a 500 mL round-bottom flask, the polymer intermediate (20.0 g) obtained in step (1), dimethyl sulfoxide (200 mL) and (3-bromopropyl)trimethylammonium bromide (51.1 g) were added and stirred at 25° C. for 48 h; the obtained dark brown viscous liquid was poured into acetone (1500 mL) and stirred thoroughly. The obtained light yellow precipitate was repeatedly washed with acetone, then washed with deionized water for several times, and dried to obtain 18.51 g of a light yellow binder. The polymer prepared in step (2) containing diphenylethane in the main chain and quaternary ammonium salt structure in the side chain had a hydrogen nuclear magnetic resonance spectrum in deuterated dimethyl sulfoxide as shown in FIG. Figure 1As shown, it can be seen that the chemical shifts of 6.5-8 ppm are related to the protons on the benzene ring, the 2.5-4 ppm signals correspond to the protons in three different chemical environments on the piperidone, and the peaks of 1.89-2.03 ppm are related to the protons on the aliphatic chain.

[0076] Example 2

[0077] This embodiment discloses a membrane electrode, the binder of which contains the polymer containing diphenylethane in the main chain and quaternary ammonium salt structure in the side chain prepared in Example 1. Specifically, the preparation method of the membrane electrode includes the following steps:

[0078] (1) A 24 wt % polymer solution containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain is diluted to 6 wt % with a mixed solvent of DMSO and anhydrous ethanol (mass ratio is 1:1) to obtain a mixed solution. Figure 2 As shown, an obvious microphase separation morphology is shown in the image. The brighter area represents the hydrophobic microdomain formed by the polymer main chain, and the darker area represents the hydrophilic microdomain composed of the quaternary ammonium salt side chain.

[0079] (2) Add NiFeP / CNTs catalyst powder to the mixed solution obtained in step (1), perform ultrasonic treatment until the catalyst powder is evenly dispersed, control the temperature below 25° C., and perform treatment for 60 minutes to obtain catalyst ink.

[0080] (3) The catalyst ink obtained in step (2) is loaded into the ultrasonic sprayer injector, and the anion exchange membrane (structure as shown in Formula IV) is adsorbed onto the high-temperature negative pressure adsorption platform of the ultrasonic sprayer. The spraying parameters are set to spray the catalyst ink onto the front of the anion exchange membrane and dry it at 80°C to obtain an anode catalyst layer with a catalyst loading of 0.4 mg / cm 2 .

[0081]

[0082] (4) Flipping the anion exchange membrane with the anode catalyst layer obtained in step (3) to the reverse side, repeating the operation described in step (3), spraying ink to the reverse side of the anion exchange membrane and drying it at 80° C. to prepare a cathode catalyst layer, thereby obtaining a membrane electrode having a polymer containing a quaternary ammonium salt side chain as a binder.

[0083] The thickness of the membrane electrode containing the polymer containing quaternary ammonium salt side chains as a binder is 84 μm. The membrane electrode has a smooth surface and uniform thickness. Scanning electron microscopy observation shows that the catalyst of the membrane electrode is evenly distributed. Figure 3 shown.

[0084] Comparative Example 1

[0085] The method for preparing a membrane electrode using a polymer containing an alkane side chain as a binder comprises the following steps:

[0086] (1) A 24 wt % alkane-containing binder solution (the alkane-containing structure is shown in Formula V) is diluted to 6 wt % with a mixed solvent of DMSO and anhydrous ethanol (mass ratio is 1:1) to obtain a mixed solution. Figure 4 As shown in the figure, a relatively obvious microphase separation morphology is presented in the image. The brighter area represents the hydrophobic microdomain formed by the polymer main chain, and the darker area represents the hydrophilic microdomain formed by the alkane side chain.

[0087]

[0088] (2) Add NiFeP / CNTs catalyst powder to the mixed solution obtained in step (1), perform ultrasonic treatment until the catalyst powder is evenly dispersed, control the temperature below 25° C., and perform treatment for 60 minutes to obtain catalyst ink.

[0089] (3) The catalyst ink obtained in step (2) was loaded into the ultrasonic sprayer injector, and the anion exchange membrane was adsorbed onto the high-temperature negative pressure adsorption platform. The spraying parameters were set to spray the catalyst ink onto the front of the membrane and dried at 80°C to obtain the anode catalyst layer. The catalyst loading was 0.4 mg / cm 2 .

[0090] (4) Flip the anion exchange membrane with the anode catalyst layer obtained in step (3) to the reverse side, repeat the operation described in step (3), spray ink to the reverse side of the anion exchange membrane and dry it at 80°C to prepare a cathode catalyst layer, and obtain a membrane electrode containing a polymer containing alkane side chains as a binder.

[0091] The thickness of the membrane electrode obtained with the polymer containing alkane side chains as a binder was 83.6 μm. The membrane surface was rough and the thickness was uniform. Scanning electron microscopy observed that the catalyst on the membrane electrode was unevenly distributed, such as Figure 5 shown.

[0092] Test example

[0093] The membrane electrodes prepared in Example 2 and Comparative Example 1 were cut into circular and square monolithic pieces with diameters of 2 cm, 5 cm×5 cm, and 1 cm×1 cm. The 2 cm diameter circular membrane electrodes prepared in Example 2 and Comparative Example 1 were first soaked in a 1 mol / L KOH solution for 24 h, and the KOH solution was replaced every 8 h. Then, polytetrafluoroethylene gaskets were used to sandwich them between H-type electrolytic cells. The membrane surface resistance and conductivity were tested using an electrochemical workstation under 30 wt% KOH solution. The measured effective area was 1.77 cm 2; Two membrane electrodes prepared in Example 2 and Comparative Example 1 with a size of 5 cm × 5 cm were prepared, and each membrane electrode was immersed in a 1 mol / L KOH solution for 24 h. The KOH solution was replaced every 8 h. Subsequently, the membrane electrodes that were not immersed and immersed in alkali solution were assembled into a single electrolytic cell, and the effective area of ​​the electrolytic cell was 20.25 cm 2 A 5 mm nickel foam gas-liquid diffusion layer was matched, and the current density of the dry membrane electrode and the membrane electrode after soaking in alkali solution was tested at a charging voltage of 2 V; the membrane electrodes prepared in Example 2 and Comparative Example 1 with a size of 1 cm×1 cm were respectively soaked in 1 mol / L KOH for 24 h, then cleaned with pure water and respectively soaked in 50 mL of 0.1 mol / L HCl for 24 h. After the HCl after soaking was fixed to volume, 10 mL was taken and titrated with 0.01 mol / L NaOH, using phenolphthalein as an indicator. After the solution changed color, the titration was stopped and the ion exchange capacity was calculated.

[0094] The data measured in the experimental example are shown in Table 1. The polymer with diphenylethane in the main chain and quaternary ammonium salt structure in the side chain disclosed in the present invention is used as a binder. Because its main chain is a diphenylethane skeleton without ether bonds, it can effectively increase the stability of the membrane electrode; at the same time, the hydrophilic quaternary ammonium salt side chain and the strongly hydrophobic diphenylethane main chain are conducive to the construction of hydrophilic and hydrophobic phase separation, thereby improving the ion exchange capacity and current density of the membrane electrode and reducing the membrane surface resistance.

[0095] Table 1 Test data

[0096]

[0097] Application of water electrolysis for hydrogen production: The membrane electrode prepared in Example 2 and Comparative Example 1 was placed in a water electrolysis hydrogen production test fixture and connected to a water electrolysis test system for testing. The LSV curves of hydrogen and oxygen evolution were measured in 1 mol / L KOH at 25°C, as shown in Figure 2. Figure 6 and Figure 7 As shown, compared with Comparative Example 1, the overpotential required for hydrogen and oxygen evolution in Example 2 is smaller, the performance is relatively excellent, and it is suitable for hydrogen production by electrolysis of water. The electrolysis current decay of the hydrogen production test by electrolysis of water is as follows Figure 8 As shown, the decay rate is slow, which can ensure the long-term operation of hydrogen production by water electrolysis.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polymer having a main chain containing diphenylethane and a side chain containing a quaternary ammonium salt structure, characterized in that: Its general formula is shown in Formula I: In formula I, x and 100-x represent molar percentages, and x is selected from 10 to 100; R is one or both of the following two structures; Wherein, m is an integer, which is selected as 0≤m≤20.

2. According to claim 1, the main chain contains diphenylethane and the side chain contains a polymer of a quaternary ammonium salt structure, characterized in that: The number average molecular weight of the polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain is 4000-17000.

3. A method for preparing a polymer containing diphenylethane in the main chain and a quaternary ammonium salt in the side chain according to claim 1 or 2, characterized in that: The following steps are involved: (1) Synthesis of polymer precursors Under the condition of -5-10°C, a diaryl alkane compound, 2,2,2-trifluoroacetophenone and N-methylpiperidone are placed in a reaction kettle, dichloromethane is added, and the reaction is carried out for 10-72 hours under the action of a super acid catalyst. After the reaction is completed, the mixture is poured into water to obtain a fibrous polymer, and the excess acid in the polymer is removed with a sodium hydroxide aqueous solution, and then washed with deionized water until neutral, and dried at 60-85°C for 12-24 hours to obtain a polymer intermediate; (2) Synthesis of quaternary ammonium polymers The polymer intermediate and the halide are added to an organic solvent, wherein the halide is a halogenated alkane or a halogenated chain quaternary ammonium salt, and the reaction is carried out at 25-80° C. for 24-48 hours. After the reaction is completed, acetone is added to precipitate a solid substance, which is washed and dried to obtain a polymer containing diphenylethane in the main chain and a quaternary ammonium salt in the side chain.

4. The method for preparing a polymer having a main chain containing diphenylethane and a side chain containing a quaternary ammonium salt according to claim 3, wherein: The molar ratio of the diaryl alkane compound, 2,2,2-trifluoroacetophenone and N-methylpiperidone in step (1) is 1:0.12-0.49:1.94-2.31; And / or, the molar ratio of the diaryl alkane compound, dichloromethane and superacid catalyst is 1:11-13:21-23; And / or, the superacid catalyst is one or more of trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid and tellurium pentafluoride; And / or, the diarylalkane compound is one or more of diphenylmethane, diphenylethane, diphenylhexane and diphenyldecane.

5. The method for preparing a polymer containing diphenylethane in the main chain and a quaternary ammonium salt in the side chain according to claim 3, characterized in that: The molar ratio of the polymer intermediate to the halide is 1:2-3; And / or, the mass ratio of the polymer intermediate to the organic solvent is 1:6-9; And / or, the volume ratio of the organic solvent to acetone is 1:3-6; and / or, the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; And / or, the halogenated alkane is one or more of methyl iodide, 1-bromobutane and 1-chloropentane; And / or, the halogenated chain quaternary ammonium salt is one or more of (3-bromopropyl)trimethylammonium bromide, (5-bromopentyl)trimethylammonium bromide and (6-bromohexyl)trimethylammonium bromide.

6. Use of a polymer comprising diphenylethane in the main chain and a quaternary ammonium salt in the side chain as claimed in claim 1 or 2 in the field of hydrogen production by water electrolysis.

7. The use according to claim 6, characterized in that: The polymer containing diphenylethane in the main chain and quaternary ammonium salt in the side chain is particularly suitable for a binder for a catalyst for hydrogen production by electrolysis of water.

8. A membrane electrode, characterized in that: The invention comprises an anion exchange membrane and a cathode catalyst layer and an anode catalyst layer respectively located on both sides of the anion exchange membrane, wherein the cathode catalyst layer and the anode catalyst layer both comprise the polymer containing diphenylethane in the main chain and a quaternary ammonium salt structure in the side chain as claimed in claim 1 or 2 and a catalyst.

9. The membrane electrode according to claim 8, characterized in that: The content of the polymer containing diphenylethane in the main chain and quaternary ammonium salt structure in the side chain in the catalytic layer is 4-6wt%; And / or, the catalyst is an active catalyst NiFeP / CNT; And / or, the loading amount of the active catalyst NiFeP / CNT in the catalytic layer is 0.4-0.8 mg / cm 2 .

10. A method for preparing a membrane electrode according to claim 8 or 9, characterized in that: The following steps are involved: The catalyst and a binder solution containing diphenylethane in the main chain and a polymer containing a quaternary ammonium salt structure in the side chain are uniformly dispersed by ultrasonic dispersion to obtain catalyst ink, and the catalyst ink is sprayed on both sides of the anion exchange membrane to prepare a membrane electrode.